2013
DOI: 10.1021/es4008933
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adsorption of Sulfamethoxazole on Suspended Carbon Nanotubes by Dissolved Humic Acid

Abstract: Although dissolved organic matter (DOM) could effectively disperse carbon nanotubes (CNTs), sorption characteristics of DOM-suspended CNTs are unclear. In this study, we evaluated the relative contribution to the overall sorption from dissolved humic acid (DHA) coating (decreased sorption) and CNT dispersion (increased sorption). We observed that the sorption coefficients of sulfamethoxazole (SMX) on DHA-suspended CNTs were up to 2 orders of magnitude higher than that on aggregated CNTs. Although the mass perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Three hypotheses were proposed. (1) Because of dispersion, the available contact area (S) between CNTs and SPAOM will be increased by sorbed SPAOM [33]. Since linear relationship was found between sorbed amount of SPAOMs (q e ) and concentration of H + (Fig.…”
Section: 2mentioning
confidence: 99%
“…Three hypotheses were proposed. (1) Because of dispersion, the available contact area (S) between CNTs and SPAOM will be increased by sorbed SPAOM [33]. Since linear relationship was found between sorbed amount of SPAOMs (q e ) and concentration of H + (Fig.…”
Section: 2mentioning
confidence: 99%
“…As a result, the interaction of CeO 2 -TiO 2 -HA is less than that of CeO 2 -HA, possibly due to adsorption competition [70]. This suggests that HA occupies some adsorption sites of these ENPs first and thus decreases the availability of "pristine" ENPs surface for further interactions [71]. HA functions as stabilizing agent by binding with nanoparticles and restricting the heteroaggregation [72].…”
Section: Interaction Of Humic Acid On the Surface Of Ceo 2 And Tio 2 mentioning
confidence: 99%
“…Also, DOM and surfactants inhibited the adsorption of phenanthrene and naphthalene on CNTs (Hu et al, 2008;. The explanations for decreased adsorption generally were the occupation of adsorption sites of CNPs due to coating by DOM or surfactants, leading to decreased availability of CNP surfaces for adsorption of organic pollutants (Pan et al, 2013). Another result was increased adsorption of organic pollutants on CNPs.…”
Section: Dissolved Organic Matter (Dom) or Surfactantsmentioning
confidence: 99%
“…The contribution of suspended CNPs to the adsorption of organic chemicals has been ignored due to the lower amounts of suspended CNPs. Thus, in our recent study (Pan et al, 2013), we tried to separate the CNTs into suspended and aggregated types. The results indicated that the apparent overall adsorption of SMX was inhibited by DOM, but the sorption coefficients of SMX on DOM-suspended CNTs were up to two orders of magnitude higher than those on aggregated CNTs.…”
Section: Dissolved Organic Matter (Dom) or Surfactantsmentioning
confidence: 99%